Cronaca familiare di Vasco Pratolini - Armellin Secchi, Giovanna (Universidad de Costa Rica, 2015)
El escritor italiano Vasco Pratolini (1913-1991) nació en Florencia en el seno de una familia proletaria. Pratolini, un hombre autodidacta, crece en el medio de la clase culta de Florencia. Cronaca Familiare, considerada su obra maestra, es una novela autobiográfica. En ella, el autor narra sus memorias desde la infancia hasta la madurez junto con su hermano, que al final muere. The Italian writer Vasco Pratolini (1913-1991) is born in Florence from a proletarian family. Pratolini, a self-educated man, grows up by getting into contact with the cultivated milieu of Florence. Family Chronicle, considered his literary masterpiece, is an autobiographic novel in which he goes through memories from childhood up to maturity together with his brother, who later dies.